Pendidikan Kejiwaan dan Kesehatan Mental (Perspektif Fakhruddin ar-Razi) - Muhammad Arif (LPPM IAIN Sultan Amai Gorontalo, 2019)
This article elaborates on Fakhruddin ar-Razi thougts about psychiatric and mental health. The research used a qualitative method. The findings showed that soul according to Fakhruddin ar-Razi, divided into three souls that are rational, emotional souls and animal. Furthermore, ar-Razi thoughts about Islamic mental health are love and romance, fairness, envy, anger, falsehood, miser and greed. All of these require Islamic therapy for healing.